Your answer would be option (1) -3x² - 18x + 19.
To find this we need to substitute in the G and F expressions into G - 3F and see what the outcome is, as this will give us the answer.
First I’m going to multiply the F expression, 2x² + 6x - 5, by 3:
3 × (2x² + 6x - 5) = 3(2x²) + 3(6x) - 3(5) = 6x² + 18x - 15.
Now we need to subtract this expression from G, which is 3x² + 4, which I will do by term:
3x² - 6x² = -3x²
0x - 18x = -18x
4 - -15 = 19
So therefore overall your answer is -3x² - 18x + 19.
I hope this helps! Let me know if you have any questions :)
8/10 because equal fractions have to be multiplied by 2
Answer:
Step-by-step explanation:
9(5 + 2)
the answer is D
-8.8 - (16.5) =
-8.8 + 16.5 =
7.7 <==
Answer:
63%
Step-by-step explanation:
12/19=0.63157895
0.63157895*100=63.1578947